Use and Production of FLOSS in Brazilian States: an Wider Survey - Lisboa, Flávio Gomes da Silva (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2024)
This article presents a quantitative and qualitative exploratory research on the use and production of free/libre and open source software (FLOSS) by Brazilian states. Each one of the 26 states and the federal district was interrogated through access to information platforms and other specific eletronic information request forms between 2023 and 2024. This research fills a gap on the use of free software by Brazilian states. This research shows which are the most used software and software categories, the licenses that occur the most, the biggest FLOSS users among the states.